Economies of destruction : how the systematic destruction of valuables created value in Bronze Age Europe, c. 2300-500 BC - Fontijn, David R. (Abingdon, Oxon ; New York : Routledge, 2019)
"Why do people destroy objects and materials that are important to them? This book aims to make sense of this fascinating, yet puzzling social practice. It does so by focusing on a period in history in which such destructive behavior reached unseen heights and complexity: the Bronze Age in Europe (c. 2300-500 BC). This period is often seen as the time in which the first 'familiar' Europe took shape due to the rise of a metal-based economy. But it was also during the Bronze Age that massive amounts of scarce and recyclable metal were deliberately buried in the landscape and never taken out again. This systematic deposition of metalwork sits uneasily with our prevailing perception of the Bronze Age as the first 'rational-economic' period in history - and therewith - of ourselves. Taking the patterned archaeological evidence of these seemingly un-economic metalwork depositions at face value, it is shown that the 'un-economic' giving-up of metal valuables was an integral part of what a Bronze Age 'economy' was about. Written as an extended essay and based on case studies from Bronze Age Europe, this book attempts to reconcile the seemingly conflicting political and cultural approaches that are currently used to understand this pivotal period in Europe's deep history. Using theories from economic anthropology, this book argues that -paradoxically - giving up that which was valuable created value. It shows that to achieve something in society, something else must be given up"--
Systematic irrationalities? The Bronze Age "destructive economy" -- Selective deposition: what does it entail and how can it be studied? -- The value conundrum: what common things and splendid items share and why their deposition is selective -- Pre-Bronze Age selective deposition -- Trade hoards: the un-economic nature of the Bronze Age metal economy -- Gifts to familiar gods? -- The receiving landscape -- Economies of destruction: "keeping-while-destroying"?
OCLC-licensed vendor bibliographic record.
Keywords: Bronze age -- Europe; Metal wastes -- Europe -- History; Economic anthropology; SOCIAL SCIENCE / Archaeology